New approaches to dental occlusion: A literature update - Franco, Ana Lúcia [UNESP]; Andrade, Marcelo Ferrarezi de [UNESP]; Segalla, José Claudio Martins [UNESP]; Gonçalves, Daniela Aparecida de Godoi [UNESP]; Camparis, Cinara Maria [UNESP] (My University, 2012)
Because the study of occlusion is a basic area in dentistry, its components, physiology and integration with the stomatognathic system (SS) have been the subject of interest in the scientific literature. However, the focus given to this issue has changed substantially. Currently, new approaches have been proposed in order to update concepts and to demonstrate the full integration and functionality of this system within the human body. With this approach, the authors proposed the following literature review aimed at gathering recent papers (published from 2000 to 2010) with innovative study design, methodology and/or results. The authors' intention is to show the main trends in the study of occlusion and the SS. The literature review was conducted in the PubMed database, using initially the term dental occlusion as a key-word. As items of interest were found, papers were grouped by categories according to their main subject matter. Forty-seven articles were selected and the main categories obtained were: 1. functional magnetic resonance imaging (fMRI); 2. brain activation; 3. masticatory/occlusal function; 4. body function and physical performance; 5. osseoperception; 6. finite element models; and 7. occlusion and pain. Observing the current literature, the authors found that recent studies present different methodologies for the study of occlusion. These studies have allowed scientists to obtain detailed information about the physiology of occlusion and the SS, as well as about its integration in the body. Research in this area should be continued in order to clarify, in detail, the role of each component of the SS and its interaction with human physiology. © 2012 by CHROMA, Inc.
Keywords: brain; dental research; face pain; finite element analysis; health status; human; mastication; pathophysiology; physiology; review; stomatognathic system; tooth occlusion; Brain; Dental Occlusion; Dental Research; Facial Pain; Finite Element Analysis; Health Status; Humans; Mastication; Stomatognathic System